2023
DOI: 10.2147/ijgm.s404696
|View full text |Cite
|
Sign up to set email alerts
|

No Association Between Ct Value and COVID-19 Severity and Mortality in Qatar

Khaleed Jemmieh,
Mohamed Tawengi,
Tamader Alyaarabi
et al.

Abstract: Background:The association between the cycle threshold (Ct) which reflects the SARS-CoV-2 viral load and the severity of COVID-19 is still not clear. We investigated the association between Ct values, symptoms and the risk of ICU admission and mortality from COVID-19 in Qatar. Methods: This case-control study used data of hospitalized individuals with confirmed COVID-19 during the period March to September 2020. Cases were defined as individuals with confirmed COVID-19 who were admitted to the intensive care u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Research has suggested that Ct values, due to their relationship with viral load, may have some value as a prognostic marker for COVID-19. Some studies have suggested an association between Ct values and adverse clinical outcomes of COVID-19 but there is still some uncertainty (17,18). In one lower Ct values were associated with severe disease and mortality (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has suggested that Ct values, due to their relationship with viral load, may have some value as a prognostic marker for COVID-19. Some studies have suggested an association between Ct values and adverse clinical outcomes of COVID-19 but there is still some uncertainty (17,18). In one lower Ct values were associated with severe disease and mortality (19).…”
Section: Introductionmentioning
confidence: 99%
“…In one lower Ct values were associated with severe disease and mortality (19). Notably, Ct values are inversely associated with viral load, with lower values indicating higher viral material in a collected sample and vice versa for high Ct values (17). Some research has suggested that a higher viral load in naso-pharyngeal areas, where samples for PCR are usually collected, is the main determinant of virologic seroconversion to infection by the SARS-CoV-2 virus.…”
Section: Introductionmentioning
confidence: 99%